A study of oral glucose tolerance in persons living in extremely high altitude places: La Rinconada, Puno, Peru - Hancco Zirena, Iván (2024)
Introduction: Under normal physiological normal conditions, high altitude inhabitants have lower blood sugar levels compared with persons living at sea level. These lower blood sugar values in high altitude are probably due to insulin. The explanation for the major glucose uptake in high altitude is not known yet. Objective: To evaluate the response to oral glucose tolerance test in healthy inhabitants of extremely high altitude areas compared to that of healthy persons living in high altitude places. To compare sensitivity to insulin using the oral glucose tolerance test in health persons living in extremely high altitude areas compared to that of healthy persons living in high altitude places. Materials and methods: This is a longitudinal, prospective and analytical study. The study group consisted in 40 healthy males living in a high altitude city (Puno, 3826 meters above sea level) and a control group including 35 healthy males living in an extremely high place for more than 5 years (Rinconada community, 5200 meters above sea level), and every subject underwent an oral glucose tolerance test. Results: Baseline blood glucose in the study group was 57.33 ± 6.08 (mg/dl); blood sugar levels after 1 hour were 82.33 ± 8.04; blood sugar values after 2 hours were 66.33 ± 4.62, and blood sugar after 3 hours was 80.75 ± 10.95 (mg/dl). In the control group, baseline blood sugar was 91.5 ± 12.11; blood sugar after 1 hour was 103.75 ± 10.5; blood sugar after 2 hours was 124.25 ± 13.1; and blood sugar after 3 hours was 80.75 ± 10.95. Conclusions: People living in extremely high altitude show blood glucose levels far below normal values, showing a differently shaped oral glucose tolerance curve compared to normal curves described in the literature.